Aerosol delivery through high-flow nasal therapy: Technical issues and clinical benefits - Calabrese, Cecilia; Annunziata, Anna; Mariniello, Domenica Francesca; Allocca, Valentino; Imitazione, Pasquale; Cauteruccio, Rosa; Simioli, Francesca; Fiorentino, Giuseppe (Frontiers in Medicine, 2023)
High-flow nasal cannula (HFNC) therapy is an oxygen delivery method particularly used in patients affected by hypoxemic respiratory failure. In comparison with the conventional “low flow” oxygen delivery systems, it showed several important clinical benefits. The possibility to nebulize drugs via HFNC represents a desirable medical practice because it allows the administration of inhaled drugs, mostly bronchodilators, without the interruption or modification of the concomitant oxygen therapy. HFNC, by itself has shown to exert a small but significant bronchodilator effect and improves muco-ciliary clearance; thus, the nebulization of bronchodilators through the HFNC circuit may potentially increase their pharmacological activity. Several technical issues have been observed which include the type of the nebulizer that should be used, its position within the HFNC circuit, and the optimal gas flow rates to ensure an efficient drug delivery to the lungs both in “quiet” and “distressed” breathing patterns. The aim of this review has been to summarize the scientific evidence coming from “in vitro” studies and to discuss the results of “in vivo” studies performed in adult subjects, mainly affected by obstructive lung diseases. Most studies seem to indicate the vibrating mesh nebulizer as the most efficient type of nebulizer and suggest to place it preferentially upstream from the humidifier chamber. In a quite breathing patterns, the inhaled dose seems to increase with lower flow rates while in a “distressed” breathing pattern, the aerosol delivery is higher when gas flow was set below the patient’s inspiratory flow, with a plateau effect seen when the gas flow reaches approximately 50% of the inspiratory flow. Although several studies have demonstrated that the percentage of the loaded dose nebulized via HFNC reaching the lungs is small, the bronchodilator effect of albuterol seems not to be impaired when compared to the conventional inhaled delivery methods. This is probably attributed to its pharmacological activity. Prospective and well-designed studies in different cohort of patients are needed to standardize and demonstrate the efficacy of the procedure.